Comparison of Electrical Properties and Endurance of Papaya Peel and Cassava Peel-Based Bio-Batteries as Potential Alternative Energy Sources - Heriansyah, Heriansyah; Rahmadani, Novia Gena; Rahman, Refpo; Ramandani, Adityas Agung (CV Media Inti Teknologi, 2025)
Background of study: Bio-batteries represent an attractive energy solution utilizing organic substances to generate electrical energy. Organic waste materials, such as fruit peels, contain electrolytic compounds harnessed for bioelectricity generation. Cassava and papaya peels, rich in natural acids and carbohydrates, offer potential as low-cost, eco-friendly materials for bio-battery development. Aims and scope of paper: This study investigates the electrical performance and endurance of biobatteries made from cassava peel and papaya peel subjected to varying fermentation durations (0, 2, and 4 days).Methods: The study employed an experimental comparative approach using 1.5 V battery casings filled with fermented cassava and papaya peel pastes. Electrical parameters (voltage, current, and power) were measured using a digital multimeter. Additionally, endurance was tested by using the biobatteries to power a 1.2 W LED until discharge.Result: Cassava peel-based biobatteries showed higher electrical output than those based on papaya peel, especially after 4 days of fermentation. The cassava battery reached a peak voltage of 1.6 V and power of 0.107 mW, while papaya reached 1.57 V and 0.105 mW. Cassava peel biobatteries also demonstrated longer endurance, operating up to 27 hours compared to 21 hours for papaya.Conclusion: Fermentation enhances the electrical properties of fruit peel biobatteries, with 4 days as the optimal duration. Cassava peel is more effective than papaya peel due to its higher content of fermentable substrates and organic acids. This study supports the feasibility of using fermented fruit waste as sustainable bio-battery material and suggests further optimization for practical applications.